2021
DOI: 10.3389/fpsyt.2021.687739
|View full text |Cite
|
Sign up to set email alerts
|

Altered Cerebral Blood Flow in Alzheimer's Disease With Depression

Abstract: Background: Depression is common in Alzheimer's disease (AD) with an unclear neural mechanism. This study aimed to investigate the underlying cerebral perfusion associated with depression in AD and evaluate its clinical significance.Method: Twenty-one AD patients and 21 healthy controls (HCs) were enrolled in this study. The depressive symptom was defined according to the Hamilton Depression Rating Scale (HAMD). Nine patients were diagnosed as AD with depression symptoms (HAMD >7). Three-dimensional pse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…On the other hand, activation of the M1-mAChR by agonists results in reduced tau phosphorylation in both primary cells and mouse brains [ 34 , 91 ]. Third, in addition to learning and memory processes, activation of M1-mAChR has been shown to improve cerebral blood flow in patients with AD [ 92 ], which is important for therapeutics development considering that disrupted blood flow is one of the most consistent and important pathological characteristics of AD pathology [ 93 ].…”
Section: M1-machr In Admentioning
confidence: 99%
“…On the other hand, activation of the M1-mAChR by agonists results in reduced tau phosphorylation in both primary cells and mouse brains [ 34 , 91 ]. Third, in addition to learning and memory processes, activation of M1-mAChR has been shown to improve cerebral blood flow in patients with AD [ 92 ], which is important for therapeutics development considering that disrupted blood flow is one of the most consistent and important pathological characteristics of AD pathology [ 93 ].…”
Section: M1-machr In Admentioning
confidence: 99%
“…These conditions can change the baseline physiological parameters, such as the baseline CBF, capillary density, blood p O 2 , and blood glucose level, which in turn can affect the response to regional blood flow obstruction. For example, it has been shown that in humans, CBF decreases with aging (up to 30% to 40% decrease) [74], mild cognitive impairment (up to 32% decrease) [74], and Alzheimer's disease (AD) (up to 25% decrease) [75]. CBF reduction has also been reported for AD murine models (13%–55% decrease) [74, 76] and an atherosclerotic mouse model [77].…”
Section: Resultsmentioning
confidence: 99%
“…The first is reduced or dysregulated cerebral perfusion. Abnormal baroreflex function and sympathetic denervation of the vasculature may both impair the regulation of cerebral perfusion ( Asil et al, 2007 ; Liau et al, 2008 ; Nasr et al, 2011 ), which has been demonstrated in chronic fatigue syndrome, Staud et al (2018) ; Li X. et al (2021) and in patients with cognitive impairment ( Li R. et al, 2021 ; Coffin et al, 2022 ; Wang et al, 2022 ). Second, reduced vagal afferent activity from baroreceptors has been associated with changes in the sleep/wake cycles ( Tsai et al, 2021 ; Karemaker, 2022 ) day-time sleepiness ( Peckerman et al, 2003 ) and reduced performance in cognitive tasks ( Reyes del Paso et al, 2004 ; Paso et al, 2012 ; Herman and Tsakiris, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Second, there is evidence that reduced BRS is associated with abnormal cerebral perfusion ( Laosiripisan et al, 2015 ). Abnormal patterns of cerebral perfusion have been demonstrated in chronic migraine, Petolicchio et al (2016) ; Bogdanov et al (2019) chronic non-migraine headache ( Gilkey et al, 1997 ; Karacay Ozkalayci et al, 2018 ), chronic fatigue syndrome ( Staud et al, 2018 ; Li X. et al, 2021 ) and impaired cognition ( Li R. et al, 2021 ; Coffin et al, 2022 ; Wang et al, 2022 ). Finally, a recent, small study examining skin biopsies of patients with migraine reported nearly 50% had evidence of small fiber neuropathy ( Stillman et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%